(untitled) (Journal of Pathology of Nepal, 2021)
Background: Pre-eclampsia and eclampsia is a multisystem disorder affecting approximately 2-7% of all pregnancies and is a significant cause of maternal and fetal morbidity and mortality. Many hemostatic abnormalities have been reported in association with hypertensive disorder of pregnancy. We conducted this prospective case-control study to assess and analyze the platelet parameters in 3rd-trimester normotensives, pre-eclamptic, and eclamptic pregnant women. Materials and methods: This study was conducted in the hematology division of the Department of Pathology, in a rural population-based medical institute over 2 years. In all subjects (cases and controls) 2 ml of blood sample was collected in EDTA vials for platelet counts and platelet indices. The blood samples were run on an automated blood cell counter (Beckman coulter) within 2 hours of collection. The data obtained were tabulated and statistical analyses were performed. Results: The mean platelet count was significantly decreased in cases as compared to controls with increased frequency of thrombocytopenia associated with progression of the disease. Platelet indices, mean platelet volume, and platelet distribution width were increased, whereas the plateletcrit was decreased in cases as compared to the controls. However, the statistically significant difference was found only in platelet distribution width and plateletcrit. Conclusions: We concluded that platelet indices like platelet distribution width and plateletcrit can be useful along with platelet count in early detection of pre-eclampsia and eclampsia instead of relying on platelet count alone.